Oral Presentations Abstracts: COMPROMISING CONFIDENTIALITY: WHERE TO STRIKE THE BALANCE? - MORGAN, James; MacKAY, Kirsty; THOMAS, Ian (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Patient confidentiality is a central tenet of medical practice, fundamental to ensuring the maintenance of trust in medical professionals. Yet are there any circumstances where a duty of care to others overrides patient confidentiality and allows disclosure of medical information without consent from the index patient? We present the case of a patient with CADASIL (Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy) a progressive, neurodegenerative condition that is inherited in an autosomal dominant manner. Admitted to ICU with a severe Traumatic Brain Injury (TBI), the patient ultimately had withdrawal of life sustaining therapy following discussion with family. The patient never regained capacity following admission and had never disclosed the diagnosis of CADASIL to his daughters. The question of whether to disclose the diagnosis to adult children and alert them to their potential risk of inheriting CADASIL (the knowledge of which could fundamentally affect their life choices) raises tensions around confidentiality and any duty of care to the patient’s daughters. Previously, for inheritable risks, the prevailing discourse gave prominence to patient confidentiality. However, a recent UK court case and professional guidance is challenging this notion. ICU clinicians faced the choice of disclosing the CADASIL diagnosis to the adult children, breaking patient confidentiality or remaining silent so allowing potential harm to befall them and even future generations. We examine the ethical issues this raises and suggest how clinicians, if faced with a similar situation in future, might proceed.